Profiling of gene expression regulated by 17β-estradiol and tamoxifen in estrogen receptor-positive and estrogen receptor-negative human breast cancer cell lines (2017)
One area of great importance in breast cancer (BC) research is the study of gene expression regulated by both estrogenic and antiestrogenic agents. Although many studies have been performed in this area, most of them have only addressed the effects of 17β-estradiol (E2) and tamoxifen (TAM) on MCF7 cells. This study aimed to determine the effect of low doses of E2 and TAM on the expression levels of 84 key genes, which are commonly involved in breast carcinogenesis, in four BC cell lines differentially expressing estrogen receptor (ER) α and HER2 (MCF7, T47D, BT474, and SKBR3). The results allowed us to determine the expression patterns modulated by E2 and TAM in ERα+ and ERα− cell lines, as well as to identify differences in expression patterns. Although the MCF7 cell line is the most frequently used model to determine gene expression profiles in response to E2 and TAM, the changes in gene expression patterns identified in ERα+ and ERα− cell lines could reflect distinctive properties of these cells. Our results could provide important markers to be validated in BC patient samples, and subsequently used for predicting the outcome in ERα+ and ERα− tumors after TAM or hormonal therapy. Considering that BC is a molecularly heterogeneous disease, it is important to understand how well, and which cell lines, best model that diversity. © 2017 Rangel et al.